Entrepreneurial Models of Inclusive Civil Culture: The Case of Zapopan Agro Ecological Park - Jose G. Vargas-Hernandez (Journal of Management Practices, Humanities and Social Sciences, 2020)
This research aims to analyze the model of entrepreneurial, inclusive civic culture created and developed in the Zapopan Agro ecological Park (PAZ). Based on the need to rescue vacant urban land use with the participation of residents residing in the surrounding colonies, social movements, civil society, and local government, they have designed and implemented actions to create PAZ (PEACE). The Zapopan Agro ecological Park is an area of green innovation where in addition to the cultivation of vegetables, vegetables, medicinal plants, and decoration under relations of cooperation, trust, and community support, the formation of social capital that sustains a culture of peace based on environmental sustainability activities. The results of the implementation of this project, born from the bottom of the social and power structures, constitute a significant experience in the regeneration of public spaces and green areas that provides greater economic efficiency in terms of family income, a greater relevance of equity, inclusion and social justice and improvement of environmental sustainability. It is concluded that Zapopan Agro ecological Park is a model of entrepreneurial, inclusive civil culture. This park marks a milestone in the regeneration of public spaces with a project of social and environmental relevance. The analysis and study of this case, Zapopan Agro ecological Park as an urban green innovation area, has the potential to connect the sphere of bio-economy with the requirements of urban development and land uses.